A ruptured cornual pregnancy: a case report - Ennasser, Hind; Raoudi, Jamal Eddine; Taheri, Hafsa; Saadi, Hanane; Mimouni, Ahmed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
A cornual gestation is a rare form of ectopic gestations accounting for 2-4% of all tubal pregnancies with a high rate of mortality among to 2%-2.5%. A 25 years old woman prima gravida was presented to the obstetrical emergency department with 8 weeks amenorrhea, lower abdominal pain and vaginal bleeding. A clinical diagnosis of ectopic pregnancy was made and confirmed using Ultrasonography and serum beta-hCG test. On laparotomy exploration authors found a left cornual ruptured ectopic pregnancy then authors made a left cornual resection with left salpingectomy. There were no postoperative complications.